Effect of Catalyst Layer Hydrophobicity on Fe−N−C Proton Exchange Membrane Fuel Cells. Issue 7 (14th April 2020) - Zhang, Xinyue; Liu, Qingtao; Shui, Jianglan
Abstract: The hydrophobicity of the cathode catalyst layer (CCL) affects the performance of the proton exchange membrane fuel cell (PEMFC) by adjusting the water management of the catalyst layer, which has been extensively studied in Pt‐based catalysts. Here, the effect of the hydrophobicity of Fe−N−C CCL on the performance of the PEMFC is investigated. The hydrophobicity of the Fe−N−C CCL is tuned by polytetrafluoroethylene (PTFE) by using three addition methods: 1) coat PTFE on Fe−N−C powder and heat‐treat; 2) mix PTFE emulsion with Fe−N−C ink and then brush the electrode; and 3) transfer a ground PTFE/Fe−N−C composite film onto the gas diffusion layer by the decal method. For each PTFE addition method, the optimized PTFE amount can increase the power density of Fe−C−N PEMFC by 15.1 %, 26.6 %, and 87.2 %, respectively. At the same time, it is found that enhanced hydrophobicity reduces the initial current decay rate of the Fe−N−C CCLs, but their residual current densities are close after a 50 h durability test at 0.5 V in a H2 ‐O2 PEMFC. It can be concluded that the hydrophobicity of the Fe−N−C CLL has a great influence on the power density of the fuel cell, but the influence on the long‐term durability of the fuel cell is negligible. Abstract : Balancing act : Polytetrafluoroethylene (PTFE) is added to different positions of the Fe−N−C catalyst layer by using three methods to adjust its hydrophobicity. An appropriate amount of PTFE in the Fe−N−C catalyst layer is beneficial to the power density of the PEM fuel cell. However, the hydrophobicity of the Fe−N−C catalyst layer does not affect the long‐term durability of the fuel cells, although high hydrophobicity will improve the fuel cell initial durability.